Role of Genetic Factors in the Etiology of Juvenile-Onset Myopia Based on a Longitudinal Study of Refractive Error - PACELLA, ROSANNA; MCLELLAN, JAMES; GRICE, KENNETH; DEL BONO, ELIZABETH A.; WIGGS, JANEY L.; GWIAZDA, JANE E. (Optometry and vision science, 1999)
In an attempt to determine the role of genetic factors in the development of myopia, we examined the relationship of infantile refractive error and parental history to juvenile-onset myopia and analyzed 43 pedigrees affected by juvenile-onset myopia. Refraction data collected at regular intervals from a sample of juvenile subjects participating in a 24-year longitudinal study of refractive error were used. Results showed that children with two myopic parents were 6.42 times as likely to become myopic as children with one or no myopic parents. Furthermore, children who had refractions in the lower half of the distribution at 6 to 12 months of age were 4.33 times as likely to develop myopia as children who had refractions in the upper half of the distribution at 6 to 12 months of age. The pedigree analysis indicated that 63% of individuals considered at risk for developing juvenile-onset myopia actually became myopic, with an equal number of affected males and females. These results suggest that juvenile-onset myopia of moderate amounts may be inherited as a complex trait involving both genetic and environmental factors.